Experimental assessment of the ability of generalist predators to control Opatrum sabulosum (Coleoptera: Tenebrionidae) - Nazimov, Serhii (Baltic Journal of Coleopterology, 2024)
Opatrum sabulosum L. (Tenebrionidae: Coleoptera) is a widespread phytophagous insect in the steppe zone, which in years of mass reproduction can cause damage to numerous crops, but is most dangerous for vegetable seedlings, as adults readily feed on wilted plant organs. As insects are increasingly developing resistance to existing synthetic insecticides and the organic farming market is growing, it is becoming increasingly important to identify new, effective and environmentally friendly means of controlling pest populations, such as the use of entomophages. Unfortunately, there are no data on invertebrate predators that are capable of natural control populations of phytophages from the Tenebrionidae family and O. sabulosum in particular. We evaluated the ability of 17 species of predators from 7 families to prey on O. sabulosum adults in a laboratory experiment. The results show that generalist predators, especially ground beetles and representatives of some other families, are capable of predation against O. sabulosum adults. The highest predation rates were recorded for Reduvius personatus, Rhynocoris iracundus, Staphylinus caesareus (100% of attacks) and Broscus cephalotes (73%). Lower predation rates were recorded for Molops piceus (40%), Harpalus rufipes (33%) and Calathus ambiguus (27%). A moderate percentage of attacks was recorded for Hister quadrimaculatus (20%) and Harpalus affinis (13%). Other entomophages did not prey on O. sabulosum during the experiments. Undoubtedly, the ground beetles B. cephalotes, H. rufipes and C. ambiguus have the potential to play a significant role in the natural control of the populations of the above-mentioned phytophagous. However, this topic undoubtedly requires further research, especially in the field.